The IARA Model as an Integrative Approach to Promote Autonomy in COPD Patients through Improvement of Self-Efficacy Beliefs and Illness Perception: A Mixed-Method Pilot Study - De Giorgio, Andrea; Dante, Angelo; Cavioni, Valeria; Padovan, Anna M.; Rigonat, Desiree; Iseppi, Francesca; Graceffa, Giuseppina; Gulotta, Francesca (Frontiers in Psychology, 2017)
Chronic obstructive pulmonary disease (COPD) is one of the most deadly and costly chronic diseases in the world characterized by many breathing problems. The management of COPD and the prevention of exacerbations are a priority goals to improve the quality of life in patients affected by this illness. In addition, it is also crucial to improve the patients’ adherence to care which, in turn, depends on their knowledge and understanding of some factors such as the prescribed medical treatment, changes in dailylife, and the process of breathing. In turn, the adherence to care leads to greater autonomy for the patient who is thus able to better manage his illness. Here we presented the application of the Model IARA in patients affected by COPD in order to achieve their autonomy in illness management which, in turn, leads to a better quality of life. IARA is an intervention program which improve the awareness and knowledge of patients with respect to both the disease and symptoms through health education. Moreover, through IARA the patients are encouraged to become more actively involved in COPD care process, also regarding drug therapy adherence. Using St. George's Respiratory Questionnaire combined with qualitative analysis, we demonstrated that IARA could be considered a useful approach in COPD management.